Cosmo City Greens: contested aspirations of ecologically sustainable lifestyles in mixed-income housing - Funde, Sinazo (Department of Environmental and Geographical Science, 2023)
This thesis is concerned with the relationship between the residents of Cosmo City, a mixedincome housing development in Gauteng, and green spaces in the development. It argues that the legacy of apartheid spatial planning has led to the unequal distribution of green infrastructure across the development, and this has disenfranchised the low-income residents. Segregation was the core of maintaining the apartheid regime. South Africans were not only divided according to race, culture and economically, but they were also divided spatially and so was the provision, proximity, and distribution of services. This segregation primarily affected the Black population negatively, as they were the ones moved to the outskirts of urban centres with little to no access to tenure or basic services. Access to green spaces was also limited as the history of South Africa was immersed in the displacement of the indigenous people out of their homes that honed their relationships between culture and nature. High economic status and access to green spaces have a positive relationship especially in the housing space. But what happens in the case of mixed-income developments? Since the change from apartheid to democracy, South Africa has implemented many housing plans and policies to undo fragmentation caused by apartheid spatial planning. Many of these plans failed over the course of implementation but their revision continues. Mixed-income housing policies have gained momentum in urban planning, especially in southern cities. These policies potentially not only bridge racial and economic disparities but they also confront issues of fragmented environmentalism through housing developments. South Africa's first mixed-income housing development, Cosmo City in Johannesburg has been the blueprint for many other mixed-income developments in the country. Cosmo City was successful in fulfilling its objectives of bringing people from the different socioeconomic backgrounds into the same neighbourhood. However, its objectives of promoting environmental sustainability across the development have not been realized. This research uses the stories of a group and middle- and low-income residents of Cosmo City as a case study to investigate the potential of mixed-income housing in South Africa to address the legacies of green apartheid through the equitable distribution of green infrastructure in mixed-income housing spaces. By investigating residents' greening aspirations, this research explores the ways in which the equitable distribution of green infrastructure in such developments can contribute to more egalitarian approaches to sustainability and facilitate social inclusion and cohesion among the residents. Qualitative research methods and desktop research were used to achieve the objectives of the study. A case study was conducted, which included regular visits to Cosmo City and open-ended interviews conducted with residents and an environmental officer from the developing company. The findings show that inequalities in the distribution and quality of green infrastructure in Cosmo City have led to reinforcing negative stereotypes and supress the livelihoods of low-income residents. In response, some residents have adopted diverse ways of breaking with the past through self-taught greening practices, even in complex situations that have already been pre-established for them. The recommendation which is made by this thesis in order promote a more holistic idea of environmental sustainability in mixed-income housing, is that stakeholders must understand the socioenvironmental dynamics of low-income residents in their respective urban spaces to accommodate their ecological needs.